DOES PALM OIL COMPANY INTERNALISE ITS STAKEHOLDER ENGAGEMENT TO ACHIEVE SUSTAINABILITY? A CASE STUDY OF DB BERHAD - Adura Ahmad; Sue Chern Ooi (International Journal of Accounting, Finance and Business, 2021)
The purpose of this study is to explore how a palm oil company, namely DB Berhad1 (thereafter DB), engages with its internal stakeholders in achieving sustainability. Interview data and annual reports of DB are analysed, and Bourdieu’s concepts of field, habitus, and capital serve as the conceptual framework of the study. The study found that due to accumulated pressures from its dominant stakeholders, such as NGOs, local and international communities, and key players within the supply chain in the palm oil industry, DB internalised its stakeholder engagement practices within the group of companies. A variety of resources, tactics, and dispositions were employed by in order to improve its sustainability practices and to gain legitimacy from its stakeholders.